PENGARUH MODEL PEMBELAJARAN RECIPROCAL DAN INTERAKSI SOSIAL TERHADAP HASIL BELAJAR PENDIDIKAN AGAMA HINDU KELAS XI SMA N 1 PENEBEL - I Made Sukma Muniksu (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2022)
Teachers are essentially expected to have the ability to process the teaching and learning process effectively and efficiently through innovative learning models by inviting students to contribute and interact with learning activities, namely by applying reciprocal learning models and social interactions that can affect learning outcomes for Hindu religious education in the classroom. XI SMA N 1 Penebel. The aims of this study are (1) to explain the effect of implementing several learning models on the learning outcomes of Hindu religious education in Class XI SMA N 1 Penebel. (2) To determine the effectiveness of the effect of the reciprocal learning model on the learning outcomes of Hindu religious education Class XI SMA N 1 Penebel. (3) To determine the effectiveness of the influence of the social interaction learning model on the learning outcomes of Hindu religious education in Class XI SMA N 1 Penebel. The population in this study were all students of class XI SMA N 1 Penebel who took Hindu religious education subjects with a sample of students of class XI IPA 2 and XI IPS 4. Collecting data using the test method in the form of multiple choice tests. Analysis of hypothesis testing using one way ANOVA and Burney t-Test. The results showed that: (1) There was an effect of the implementation of several learning models on the learning outcomes of Hindu religious education in Class XI SMA N 1 Penebel which can be seen in the results of the analysis of Hindu religious education learning outcomes in the experimental group with the reciprocal learning model having an average of 86,7. The experimental group with the social interaction learning model has an average of 83,2 and the control group with the conventional learning model has an average of 74,6. (2) The reciprocal learning model has an effective effect on the learning outcomes of Hindu religious education in class XI SMA N 1 Penebel. (3) The social interaction learning model has an effective effect on the learning outcomes of Hindu religious education in class XI SMA N 1 Penebel.Keywords: Reciprocal, Social Interaction, Hindu Religious Education